Evaluating China's role in contemporary South American trade - an economic complexity approach - Linus Zechlin; Moritz Marpe (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The rapidly expanding importance of the Chinese economy saw a restructuring of the global trade hierarchy. While this proves challenging for all economic actors, especially peripheral economies are forced to rethink the way they interact and trade with the new emerging economy (EME) powerhouse that is China. In this article, we pay closer attention to the South American (SAC) economies and their specific industrial composition that arguably left them in an unequal relationship with China, placing them in a precarious situation of dependency on low-complexity commodities. Utilising the theoretical framework of economic complexity, we thoroughly assess this asymmetric relationship between SAC and China. Causal linkages are further created by including the findings from this descriptive examination into a structural gravity model of trade. We find that the complexity approach underlines the notion of asymmetry in the Chinese-SAC trade nexus and places the latter in a so-called quiescence trap, a disposition which could be outgrown by a significant increase in productive capabilities. The econometric analysis reinforces this, urging additional research on other developing and emerging economies.
Keywords: F10; F14; O53; 330; International Trade; Economic Complexity; Gravity Theory; China; South America